Gerenciamento de Faltas em Computação em Nuvem: Um Mapeamento Sistemático de Literatura - Leite Neto, Clodoaldo Brasilino (2014)
Background: With the growing popularity of cloud computing, an challenge seen in this discipline is the management of faults that may occur in such big infrastructures that, because of its size, has a greater chance of ocurring faults, errors and failures. A work that maps the solutions already created by researchers efficiently should help visualizing gaps over those research fields. Aims: This work aims to find research gaps in the cloud computing and fault management domains, aside from building a social network of researchers in the area. Method: We conducted a systematic mapping study to collect, filter and classify scientific works in this area. The 4535 scientific papers found on major search engines were filtered and the remaining 166 papers were classified according to a taxonomy described in this work. Results: We found that IaaS is most explored in the selected studies. The main dependability functions explored were Tolerance and Removal, and the attributes were Reliability and Availability. Most papers had been classified by research type as Solution Proposal. Conclusion: This work summarizes and classifies the research effort conducted on fault management in cloud computing, providing a good starting point for further research in this area.